1994
DOI: 10.1093/geront/34.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Living Alone With Alzheimer's Disease: Effects on Health and Social Service Utilization Patterns

Abstract: Subjects with possible or probable Alzheimer's disease who live alone are more likely to be women, and more likely to be poor than those living with others. They are also older and have milder cognitive impairments and a shorter disease duration. Living arrangement is a significant predictor of service utilization even with other factors held constant. Subjects living alone were less likely to use medical services such as physicians and hospitals, and more likely to use services such as homemaker chore and hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
7
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 0 publications
6
65
7
2
Order By: Relevance
“…In addition, our data indicate that PWD living alone did not seem to have more health risks-they did not differ from those not living alone regarding depression, quality of life, falls, drug related problems, or malnutrition. Thus, our findings do not agree with the results of former studies that showed that PWD living alone are less cognitively and functionally impaired, and at the same time are at a higher risk for health problems [3,[5][6][7]. A possible explanation for these discrepancies could be differences in the study samples.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In addition, our data indicate that PWD living alone did not seem to have more health risks-they did not differ from those not living alone regarding depression, quality of life, falls, drug related problems, or malnutrition. Thus, our findings do not agree with the results of former studies that showed that PWD living alone are less cognitively and functionally impaired, and at the same time are at a higher risk for health problems [3,[5][6][7]. A possible explanation for these discrepancies could be differences in the study samples.…”
Section: Discussioncontrasting
confidence: 99%
“…The majority of these patients were widowed (70%), implying that a major reason for living alone was the death of the patients' spouse. These findings are in line with the results of previous studies [3,[5][6][7]. Surprisingly, regarding the clinical variables examined we did not find any statistically significant differences between PWD who lived alone and those who did not.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As these individual age, they are also likely to develop a dementing illness [18,28,29]. In contrast to a previously described population of AD patients who were living alone [30], we found no significant difference in mean subject age between those living alone and those living with a caregiver. Our population was quite a bit older (i.e.…”
Section: Discussioncontrasting
confidence: 97%